Topical and ingested cooling methodologies for endurance exercise performance in the heat - Best, R.; Payton, S.; Spears, I.; Riera, F.; Berger, N. (Sports, 2018)
This systematic review and meta-analysis aimed to assess studies which have investigated cooling methodologies, their timing and effects, on endurance exercise performance in trained athletes (Category 3; VO2max = 55 mL·kg·min-1) in hot environmental conditions (=28 °C). Meta-analyses were performed to quantify the effects of timings and methods of application, with a narrative review of the evidence also provided. A computer-assisted database search was performed for articles investigating the effects of cooling on endurance performance and accompanying physiological and perceptual responses. A total of 4129 results were screened by title, abstract, and full text, resulting in 10 articles being included for subsequent analyses. A total of 101 participants and 310 observations from 10 studies measuring the effects of differing cooling strategies on endurance exercise performance and accompanying physiological and perceptual responses were included. With respect to time trial performance, cooling was shown to result in small beneficial effects when applied before and throughout the exercise bout (Effect Size: -0.44; -0.69 to -0.18), especially when ingested (-0.39; -0.60 to -0.18). Current evidence suggests that whilst other strategies ameliorate physiological or perceptual responses throughout endurance exercise in hot conditions, ingesting cooling aids before and during exercise provides a small benefit, which is of practical significance to athletes` time trial performance.